2011
DOI: 10.17969/agripet.v11i2.367
|View full text |Cite
|
Sign up to set email alerts
|

Prediksi Bobot dan Konformasi Karkas Kambing Lokal Mengunakan Prediktor Bobot Potong dengan Berbagai Model Regresi

Abstract: The goat population of Indonesia is concentrated in Central Java province especially under smallholder farming areas, and mostly their function is the production of meat. Local breed (Jawa Randu and Peranakan Etawah Crossbred) are very common raised by samallholders in Banyumas areas. The local kids are raised with their mothers and slaughtered after post weaning (6-8 months old). Carcass characteristics are important criteria for consumers and it could be taking into account. The objective of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
1
2
Order By: Relevance
“…The average carcass percentage of male Kacang goat was 48.12±0.28% (Table 1). This result was higher than carcass percentage of 2 years old Kacang goat reported by Sunarlim and Usmiati, 2006) Sodiq (2011) that Kacang goat at 10-23,5 kg of weight produced carcass about 44.09±1.98%. Soeparno (2015) observed that the higher of body weight, weight of carcass would be increased.…”
Section: Carcass Quality Of Male Kacang Goatcontrasting
confidence: 59%
“…The average carcass percentage of male Kacang goat was 48.12±0.28% (Table 1). This result was higher than carcass percentage of 2 years old Kacang goat reported by Sunarlim and Usmiati, 2006) Sodiq (2011) that Kacang goat at 10-23,5 kg of weight produced carcass about 44.09±1.98%. Soeparno (2015) observed that the higher of body weight, weight of carcass would be increased.…”
Section: Carcass Quality Of Male Kacang Goatcontrasting
confidence: 59%
“…Local goats with weaning age (6-18 months) with a range of weights of 10-23.5 kg (mean 15.99 kg) produce carcass weight from 4.5 to 10 kg (mean 7.05 kg) and carcass percentage 44.68-45% (average 44.09%). These results are who observed goats in Majalengka and Bandung regencies with live weights of 14.99-18 kg (6.3-22.1 and 16-21 kg) resulting in carcass weight 7.23 -7.58 kg and carcass percentage 48.23-42, 10 percent [23] Non carcasses produced from treatment P1, P2, P3, and P4 if rounding is the same value, namely 65 %, 60 %, 61% and 61, the highest is treatment P1 which is 65.17 or 65 percent while P2 is 60%, P3 and P2 are relatively the same, namely 61 %. This means that parts of the carcass that the highest low economic value in treatment P1.…”
Section: Resultssupporting
confidence: 65%
“…other factors that influence the percentage of the carcass are a nation, sex, slaughter weight and feed [34]. Furthermore, it was reported that the percentage of goat carcasses was 39.39% -42.48% and 44.68-45% [23].…”
Section: Resultsmentioning
confidence: 99%
“…The weight of body and carcass of this finding were higher than those of Sodiq [18] which body and carcass weight of Jawarandu bucks aged 6-18 months were 16.0 kg and 7.05 kg, respectively. The differences of these results might due to the difference of rearing system and nutrient intake.…”
Section: Body Measurements and Productivitycontrasting
confidence: 51%